ECLAC and the sociology of development - Enzo Faletto (CEPAL Review, 1996)
The principal sphere in which ECLAC’S theses are situated is that of economics. However, as befits an integrated approach to development, the theories it has propounded also include sociological and political aspects. The social aspects of development have been a focus of attention at ECLAC since its creation, and in this area too it has endeavoured to avoid the mechanical transposition of existing theories to the region. Through an interchange of ideas with specialists from other institutions, it has sought to identify the specifically regional dimension of the problems dealt with and to determine the precise social and political conditions conducive to economic development.